Molecular docking and molecular dynamics study on potential ebola matrix protein VP40 inhibitors - Mohamad Ariff bin Mohamad Yussoff (Kulliyyah of Science, International Islamic University Malaysia, 2019)
It is well known that Ebola virus (EBOV) causes severe haemorrhagic fever with high fatality rate. The biggest Ebola outbreak in 2014 has caused at least 11,323 deaths with more than 28,000 cases have been reported. Studies have demonstrated that EBOV matrix protein known as VP40 is crucial in the early infection stage to facilitate the transcription of the viral gene through association with ssRNA in specific manner. Two residues namely Phe125 and Arg134 were found to be important in mediating the VP40-RNA interaction. Thus, blocking this VP40-RNA interaction could interrupt EBOV life cycle in the host cell. This study aims to identify and optimise ligands that can potentially block the RNA binding site of VP40. A total of 42 previously studied ligands from literature were simulated against the RNA binding site using AutoDock Vina. The top ten ligands were used as templates for similarity search in ZINC databases using USRCAT followed by structure-based virtual screening at the RNA binding site and molecular dynamics simulation. The ADME properties of the compounds were predicted computationally and the binding free energy of the complex was calculated using molecular-mechanics Poisson Boltzmann surface area (MM-PBSA) method. Our results showed that Q-88 (ZINC ID: 1342431) turned out to be the best-docked compound with binding free energy of -97.27 kJ/mol. However, this compound gave unsatisfactory ADME properties by violating two Ghose's rule and has low GI absorption. Substituting the sulphur (S) atom with oxygen (O) in the backbone structure of Q-88 eliminated the drug-likeness violation and improved GI absorption prediction with similar binding free energy (-97.097 kJ/mol). This finding shed light on binding energies and potential modification of previously tested compounds against Ebola VP40, which could be useful to design more potent and drug-like VP40 inhibitors.